Commercial victimisation survey, 2022 (UK Data Service, 2023)
The Commercial Victimisation Survey, 2022 aims to estimate the extent and nature of crime affecting all commercial business premises in England and Wales. The data includes the prevalence and frequency of crime affecting business premises in England and Wales: as well as impacts on premises, crime prevention measures taken up by premises, experiences of the police, and attitudes to the police.